2017
DOI: 10.1016/j.psyneuen.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Social status strategy in early adolescent girls: Testosterone and value-based decision making

Abstract: a b s t r a c tThere has been strong interest, spanning several disciplines, in understanding adolescence as a developmental period of increased risk-taking behavior. Our goals focus on one line of investigation within this larger developmental risk framework. Specifically, we examined levels of pubertal hormones in girls in relation to their willingness to take greater financial risks to gain social status. To this end, we tested the hypothesis that higher levels of testosterone during the ages of pubertal ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 46 publications
1
21
1
Order By: Relevance
“…The sharp rise in testosterone at the onset of puberty in both boys and girls is associated with shifts in social and affective information processing 70,[93][94][95] and increased prioritization of social status feedback 93 . A recent review of decades of research into the behavioral effects of testosterone in animals and humans concluded that testosterone increases 'motivation to gain social status' 96 .…”
Section: Developmental Timing Investments and Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sharp rise in testosterone at the onset of puberty in both boys and girls is associated with shifts in social and affective information processing 70,[93][94][95] and increased prioritization of social status feedback 93 . A recent review of decades of research into the behavioral effects of testosterone in animals and humans concluded that testosterone increases 'motivation to gain social status' 96 .…”
Section: Developmental Timing Investments and Interventionsmentioning
confidence: 99%
“…Establish healthy bone 'bank' through optimal calcium, vitamin D , and exercise 40 Increased tendency to explore, seek novelty & excitement •Create opportunities for positive risk taking resulting in healthy, positive, productive, high arousal learning 102,103 •Provide context for self-directed, discovery/ exploratory learning Pubertal changes in sleep and circadian regulation •Couple later school start times with prevention and intervention efforts to improve and regularize sleep 123 •Provide sleep interventions to youth at increased risk for mental health problems 124 Motivation for status, prestige, and respect •Design health promotion and behavioral interventions in ways that honor adolescents' sensitivity to autonomy, respect and prestige 105 •Train adult teachers/facilitators to treat adolescents with respect and appropriately enhance autonomy 125Motivation for social learning •Leverage social relationships to reinforce positive behavior93,97 •Support adolescents in processing social information and understanding social experiences •Structure learning experiences to include, rather than ignore, social context 72,Create mastery curve learning opportunities that gradually become more challenging…”
mentioning
confidence: 99%
“…In particular, although adolescents have more accumulated experience than younger children, there is evidence, as noted above, that adolescence may also be a period of enhanced plasticity and learning (59,60), especially for social domains (32,61), in part through the privileging of social information processing and the salience of social rewards in decision making (62,63). Cultural innovations, such as new socially significant forms of language, dress, or music often first appear in adolescents.…”
Section: Continuous Knowledge Acquisition Vs Discontinuous Developmementioning
confidence: 99%
“…Thus, future research should also investigate how changes in the (social) environment due to factors like an individual's physical changes after pubertal onset may impact mechanisms of plasticity and learning. In addition, pubertal hormones also play an important role in developmental changes in social motivational processes, leading to an increase in socially motivated behavior (Cardoos et al, 2017;Crone & Dahl, 2012). This increased motivation for social goals may also facilitate learning in higher cognition.…”
Section: Reliable Measures Of Plasticity-related Changesmentioning
confidence: 99%